Visuospatial memory in apraxia: Exploring quantitative drawing metrics to assess the representation of local and global information. - Salo, Sarah K.; Harries, Cathryn A.; Riddoch, M. Jane; Smith, Alastair D. (Memory & Cognition, 2025)
Neuropsychological evidence suggests that visuospatial memory is subserved by two separable processing systems, with dorsal underpinnings for global form and ventral underpinnings for the integration of part elements. Previous drawing studies have explored the effects of Gestalt organisation upon memory for hierarchical stimuli, and we here present an exploratory study of an apraxic dorsal stream patient's (MH) performance. We presented MH with a stimulus set (previously reported by Riddoch et al., Cognitive Neuropsychology, 20(7), 641-671, 2003) and devised a novel quantitative scoring system to obtain a finer grain of insight into performance. Stimuli possessed either good or poor Gestalt qualities and were reproduced in a copy condition and two visual memory conditions (with unlimited viewing before the model was removed, or with 3 s viewing). MH's copying performance was impaired in comparison to younger adult and age-matched older adult controls, with a variety of errors at the local level but relatively few at the global level. However, his performance in the visual memory conditions revealed impairments at the global level. For all participants, drawing errors were modulated by the Gestalt qualities of the stimuli, with accuracy at the global and local levels being lesser for poor global stimuli in all conditions. These data extend previous observations of this patient, and support theories that posit interaction between dorsal and ventral streams in the representation of hierarchical stimuli. We discuss the implications of these findings for our understanding of visuospatial memory in neurological patients, and also evaluate the application of quantitative metrics to the interpretation of drawings.